Electromagnetic processes in the power seсtion of the series-to-series resonant converter for contactless inductive energy transfer = Электромагнитные процессы в силовой части последовательно-последовательного резонансного преобразователя для бесконтактной индуктивной передачи электроэнергии - Pavlov, H. V.; Obrubov, A. V.; Pokrovskyi, M. V.; Vinnychenko, I. L.; Павлов, Г. В.; Обрубов, А. В.; Покровский, М. В.; Винниченко, И. Л. (My University, 2017)
The paper analyzes the electromagnetic processes in the power section of the series-to-series resonant converter for contactless inductive energy transfer. Static characteristics or the converter are discussed. The state-variable method has been implemented to solve the vector-matrix equations describing the processes in the power section of the converter, which allowed obtaining the dependence of the average value of the output current on the parameters of the circuit elements, the load, and the size of the transformer gap. There have been also obtained the load and adjustment characteristics of the converter. The research results can be applied in the development of a converter control system. The adjustment characteristics are established for a sufficiently large interval with a large air gap; they are of a linear form. The load characteristics are quite rigid, which simplifies control of the converter’s output current = Проанализированы электромагнитные процессы в силовой части последовательно-последовательного резонансного преобразователя для бесконтактной индуктивной передачи энергии. Получены решения векторно-матричных систем уравнений, описывающих электромагнитные процессы в силовой части резонансного преобразователя для бесконтактного электропитания. Получена зависимость среднего значения выходного тока преобразователя от параметров элементов резонансных контуров, величины воздушного зазора трансформатора, параметров источника и нагрузки. Построены статические характеристики последовательно-последовательного резонансного преобразователя.
Electromagnetic processes in the power seсtion of the series-to-series resonant converter for contactless inductive energy transfer / H. V. Pavlov, A. V. Obrubov, M. V. Pokrovskyi, I. L. Vinnychenko // Shipbuilding & Marine Infrastructure. – 2017. – № 2(8). – P. 70–76.
Keywords: two-circuit resonant converter; contactless energy transfer; state-variable method; static characteristics; двухконтурный резонансный преобразователь; бесконтактная передача энергии; метод переменных состояния; статические характеристики